THE EFFECT OF LEADERSHIP, WORK DISIPLIN ON EMPLOYEE PERFORMANCE TROUGH ORGANIZATIONAL COMMITMENT AS MEDIATION VARIABLES - Bagis, Fatmah; Darmawan, Akhmad; Hidayah, Arini (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
This study aims to analyze the effect of leadership, work discipline on performance through organizational commitment as a mediating variable. This research is a case study at a workshop company in Purwokerto and respondent from this study were 100 employee from supervisor and technical staff. This study used data analysis techniques namely PLS (Partial Least Square) analyisis using Smart PLS 3.0. The results showed that the leadership had a negative and no significant effect on organizational commitment, work discipline had a negative and significant effect on organizational commitment. The results also show that organizational commitment has a positive and significant effect on employee performance. The results showed that work discipline has a positive and significant effect on employee performance and leadership has a positive and significant effect on employee performance. The results showed that organizational commitment cannot mediate between leadership and work discipline on employee performance.